Synthesis and evaluation of frentizole-based indolyl thiourea analogues as MAO/ABAD inhibitors for Alzheimer's disease treatment - Hroch, Lukas; Guest, Patrick; Benek, Ondrej; Soukup, Ondrej; Janockova, Jana; Dolezal, Rafael; Kuca, Kamil; Aitken, Laura; Smith, Terry K; Gunn-Moore, Frank; Zala, Dominykas; Ramsay, Rona R; et al. (Bioorganic & medicinal chemistry, 2017)
Alzheimer's disease (AD) is a neurodegenerative disorder associated with an excessive accumulation of amyloid-beta peptide (Aβ). Based on the multifactorial nature of AD, preparation of multi-target-directed ligands presents a viable option to address more pathological events at one time. A novel class of asymmetrical disubstituted indolyl thioureas have been designed and synthesized to interact with monoamine oxidase (MAO) and/or amyloid-binding alcohol dehydrogenase (ABAD). The design combines the features of known MAO inhibitors scaffolds (e.g. rasagiline or ladostigil) and a frentizole moiety with potential to interact with ABAD. Evaluation against MAO identified several compounds that inhibited in the low to moderate micromolar range. The most promising compound (19) inhibited human MAO-A and MAO-B with IC50 values of 6.34μM and 0.30μM, respectively. ABAD activity evaluation did not show any highly potent compound, but the compound series allowed identification of structural features to assist the future development of ABAD inhibitors. Finally, several of the compounds were found to be potent inhibitors of horseradish peroxidase (HRP), preventing the use of the Amplex™ Red assay to detect hydrogen peroxide produced by MAO, highlighting the need for serious precautions when using an enzyme-coupled assay.
Keywords: Dose-Response Relationship, Drug; fenylmočovinové sloučeniny; Structure-Activity Relationship; Enzyme Inhibitors; 3-hydroxyacyl-CoA-dehydrogenasy; Molecular Structure; Monoamine Oxidase; molekulární struktura; 3-Hydroxyacyl CoA Dehydrogenases; Thiourea; benzothiazoly; monoaminoxidasa; Alzheimer Disease; inhibitory enzymů; Phenylurea Compounds; vztahy mezi strukturou a aktivitou; Alzheimerova nemoc; thiomočovina; lidé; Benzothiazoles; Humans; vztah mezi dávkou a účinkem léčiva